Pengelolaan Arsip Dinamis di Lembaga Pendidikan SMA Negeri 1 Babakan Kabupaten Cirebon - Gunawan, Rian; Sukaesih, Sukaesih; Romaddyniah, Lusi (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
This study aims to find out how active dynamic archive management includes creation, arrangement, use, and storage activities, as well as knowing the supporting and inhibiting factors in active dynamic archive management activities at SMAN 1 Babakan, Kabupaten Cirebon. This research uses a qualitative approach with descriptive methods. Data collection techniques were carried out in three ways, namely field observations, direct interviews, and literature studies. The informants specified in this study were archivists at the Administration Office of SMAN 1 Babakan. The results of this study indicate that active dynamic archive management at SMAN 1 Babakan is carried out in several stages, (1) creation and acceptance; (2) checking and filing; (3) storage; (4) maintenance and security; (5) use; (6) transfer and destruction of archives. Records management is carried out on a mixed principle (centralized and decentralized) where some archives are managed by the respective work units and some are managed at the central archives. The management of dynamic archives receives support from the school in the form of providing adequate archive management support facilities. Then the obstacle that is felt is in the competence of Human Resources which is still minimal because it is still very new, so that archive management is not fully in accordance with existing standards.